Analysis of participation of law enforcement forces in providing security at football matches and generalization of potential risks that might emerge during EURO-2012 Finals in Ukraine - Kyrylenko V. А.; Pozhydayev А. О. (Honor and Law, 2019)
Statistics on high profile cases that took place during football matches in the world, the number of law enforcement forces that were allocated to ensure law and order during mass gatherings and generalization of the potential risks that might emerge during EURO-2012 Finals in Ukraine are given.